The Economics & Psychology of Inequality and Human Development - Flavio Cunha
Recent research on the economics of human development deepens under- standing of the origins of inequality and excellence. It draws on and contributes to personality psychology and the psychology of human development. Inequal- ities in family environments and investments in children are substantial. They causally aect the development of capabilities. Both cognitive and noncognitive capabilities determine success in life but to varying degrees for dierent out- comes. An empirically determined technology of capability formation reveals that capabilities are self-productive and cross-fertilizing and can be enhanced by investment. Investments in capabilities are relatively more productive at some stages of a child's life cycle than others. Optimal child investment strategies dier depending on target outcomes of interest and on the nature of adversity in a child's early years. For some congurations of early disadvantage and for some desired outcomes, it is ecient to invest relatively more in the later years of childhood than in the early years.inequality, capabilities, noncognitive traits, human development, technology of capability formation, policy targeting